2019
DOI: 10.1038/s42003-019-0424-4
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus maintains healthy gut mucosa by producing L-Ornithine

Abstract: Gut mucosal layers are crucial in maintaining the gut barrier function. Gut microbiota regulate homeostasis of gut mucosal layer via gut immune cells such as RORγt (+) IL-22(+) ILC3 cells, which can influence the proliferation of mucosal cells and the production of mucin. However, it is unclear how gut microbiota execute this regulation. Here we show that lactobacilli promote gut mucosal formation by producing L-Ornithine from arginine. L-Ornithine increases the level of aryl hydrocarbon receptor ligand L-kynu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 49 publications
1
58
0
Order By: Relevance
“…Lactobacillus are acid-lactic producing bacteria and belong to the Firmicutes phylum, the second most prevalent in the human gut ( 39 ). Recently, a study showed that Lactobacillus promote gut barrier integrity by producing L-Ornithine from arginine amino acid ( 40 ). We suggest that this increase in Lactobacillus in patients with no hormone replacement could be associated with the small intestinal bacterial overgrowth (SIBO) in patients with HT ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus are acid-lactic producing bacteria and belong to the Firmicutes phylum, the second most prevalent in the human gut ( 39 ). Recently, a study showed that Lactobacillus promote gut barrier integrity by producing L-Ornithine from arginine amino acid ( 40 ). We suggest that this increase in Lactobacillus in patients with no hormone replacement could be associated with the small intestinal bacterial overgrowth (SIBO) in patients with HT ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that L-ornithine administered to mice resulted in goblet cell production, mucin secretion and cell proliferation, which are associated with a healthier gut environment (Qi et al, 2019 ). Together with these results, L-ornithine also induces accumulation of IL-22 in intestinal tissues (Qi et al, 2019 ), a cytokine involved in the reconstitution of gut epithelial cells, improving mucus production by goblet cells, increasing the production of antimicrobial peptides and modulating genes involved in wound healing (Sun et al, 2012 ). Overall, these observations suggest that histamine and L-ornithine might be important signaling molecules in DEC pathogenesis and merit further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Glycerol degradation pathways are enriched in gut microbiotas of people with functional constipation 47 , elevated levels and cross-feeding of microbially derived formate have been associated with inflammation 48 , and levels of succinate as well as microbes producing or consuming it have been associated with obesity and related diseases 49 . Exchange of niacin (B3) and its importance for microbiota stability are supported by in silico, in vitro, and in vivo evidence 40,50,51 , and microbial ornithine production promotes healthy gut mucosa through crosstalk with the host 52 . Thus, the predicted exchanges appear plausible, and they amount to hypotheses on specific producers and consumers, which are hard to identify experimentally.…”
Section: Metabolite Exchanges In the Human Gutmentioning
confidence: 98%